Pathways between BMI and adherence to weight management in adolescence - Pereira, Cícero Roberto (2018)
Prioste, A., Fonseca, H., Pereira, C. R., Sousa, P., Gaspar, P., Do Céu Machado, M. (2017). Pathways between BMI and adherence to weight management in adolescence. International Journal of Adolescent Medicine and Health, 29 (6)